Potential of Soursop Leaf Extract (Annona Muricata L.) as an Antimicrobial Against Staphylococcus epidermidis - Fauziy, Aqil; Waspodo, Nurelly N.; Irwan, Andi Alamanda; Sodiqah, Yani; Karina, Dhian; Harahap, Muhammad Wirawan (International Journal of Health Science and Technology, 2025)
Staphylococcus epidermidis is an opportunistic bacterium that can cause infections, particularly in individuals with weakened immune systems. The increasing resistance to antibiotics has encouraged the use of medicinal plants such as soursop leaves (Annona muricata L.), which contain antibacterial compounds. This study aims to evaluate the antibacterial effectiveness of soursop leaf extract against the growth of Staphylococcus epidermidis at concentrations of 50%, 75%, and 100%. The study specifically investigated the inhibition zones formed at each concentration (50%, 75%, and 100%) of Annona muricata L. extract against Staphylococcus epidermidis, and compared the antibacterial activity across these three concentrations. This research used a laboratory experimental design with the Kirby-Bauer disc diffusion method to assess the antibacterial activity. The extract was prepared using 96% ethanol and tested at the concentrations stated. Gentamicin 10 μg was used as a positive control, while sterile distilled water served as the negative control. The inhibition zones were observed after 24 hours of incubation at 37°C. The results showed that soursop leaf extract at 50% and 75% concentrations produced inhibition zones categorized as resistant. At 100% concentration, the inhibition zone ranges from resistant to intermediate. The comparison across all three concentrations indicates that the 100% concentration demonstrated notable antimicrobial activity against Staphylococcus epidermidis.